Implications of the Existence of an Adaptive Organizational Culture in the Establishment of the Leadership Market Value Applied Study of the Views of a Sample of Industrial Project Leaders in The Holy Hussaini Shrine - Hameedah Ghjaer Gremikh; Prof. Dr. Ihsan Dahash Chalab (Scholars Digest Publishing, 2023)
The purpose of the current study is to demonstrate the effect of an organization's adaptive organizational culture in its dimensions (values of change, orientation towards procedures) and the creation of a market value for leadership in its dimensions (individual dimension and organizational dimension) for a sample of industrial project leaders at the Holy Shrine of Al-Hussainiya. The questionnaire was utilized to gather data from the study sample, as (160) questionnaires were issued and 150 questionnaires were valid for analysis. Statistical approaches were used to assess the findings and test hypotheses on the relationship between variables. The study resulted in a series of findings and suggestions, the most significant of which was that the directors of research projects should devote more resources (time/efforts, money, etc.) to it, hence increasing its market value.
Keywords: adaptive organizational culture, market value of leadership, change values, action orientation.